Lady Mary Wortley Montagu and Ahmed Beg of Kumodraž - Filipović, Nenad (Prilozi za orijentalnu filologiju, 2017)
In this paper were analyzed the data in the letters of Lady Mary Wortley Montagu (d. 1762) describing her stay in Belgrade in 1717 in the house of the local notable and intellectual, Ahmed Beg of Kumodraž. Ahmed Beg was identified via comparison of the data in Lady Mary’s letters with those in the Epistolary Collection of Tımışvarli ‘Osmān Āġā and in the documents of the Court War Council in Vienna. It was given the overview of Ahmed Beg’s ideas and they were identified as characteristical for the Ottoman salon culture (mecālis) and as an expression of the continuous presence of the Islamic philosophy proper in the Ottoman culture. It was brought to attention the enormous importance of the Islamic categories of privacy and of the Islamic legal and moral norms protecting one’s right to privacy. Conclusion is that these categories and norms were the basis of both the intellectual and cultural development and freedom in the Islamic world in general and in the Ottoman Empire in particular. The contacts of Ahmed Beg of Kumodraž and the Anglo-Irish radical deist Dr Toland were brought to light, also. The main thesis of paper for which evidence has been produced can be summarized as following: the interconfessional and intercommunal intellectual-cultural contacts, i. e. contacts in the socalled sphere of the high culture, in the Ottoman Empire indeed existed. This applies both to the contacts between local Muslims and non-Muslims as well as to the contacts between subjects of the Ottoman Empire and foreigners visiting the Ottoman Empire. Besides, the paper, as a case-study, proved the high evidentiary value of the collection known as The Turkish Embassy Letters whose author was Lady Mary Wortley Montagu.